(N~ELOWE^ESKIJ FAKTOR W QZYKE (B: (NqZYK I POROVDENIE RE^I (B/s - (N{AHNAROWI^(B, (NaLEKSANDR mARKOWI^s; (NsAHARNYJ(B, (NlEONID wOLXKOWI^s; (NkUBRQKOWA(B, (NeLENA sAMOJLOWNAs; (NiN(B-(NT QZYKOZNANIQ an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1991)
(NbIBLIOGR(B. (NW KONCE RAZDELOWs
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NrE^EWAQ DEQTELXNOSTXs; (NqZYK I MY[LENIEs